High‐dose recombinant human bone morphogenetic protein‐2 impacts histological and biomechanical properties of a cervical spine fusion segment: results from a sheep model. (5th June 2015) - Pobloth, Anne‐Marie; Duda, Georg N.; Giesecke, Moritz T.; Dienelt, Anke; Schwabe, Philipp
Abstract: The 'off‐label' use of high‐dose recombinant human bone morphogenetic protein‐2 (rhBMP‐2) in lumbar and cervical fusion leads to heterotopic bone formation and vertebral osteolysis. These radiographically assessed side‐effects in patients were frequently associated with an over‐dosage of BMP‐2. However, little is so far known about the histological, functional or biomechanical tissue consequences of over‐dosage of rhBMP‐2 in these specific clinical situations. We hypothesized that a high dose of rhBMP‐2 in cervical spinal fusion could induce substantial alterations in bone, leading to mechanical impairment. An anterior cervical spinal fusion (C3–C4 ACDF) model in 16 sheep (aged > 2.5 years; n = 8/group) was used to quantify the consequences of a high rhBMP‐2 dose (6 mg rhBMP‐2) on fusion tissue compared to the 'gold standard' of autologous, cancellous bone graft. The fusion site was assessed by radiography after 0, 8 and 12 weeks. Biomechanical non‐destructive testing and (immuno)histological and histomorphometrical analyses were performed 12 weeks postoperatively. Although high‐dose rhBMP‐2 treatment led to an advanced radiological fusion result compared to autograft treatment, heterotopic bone formation and vertebral bone resorption were induced simultaneously. Histological evaluation unveiled highly active bone‐forming processes ventral to the fusion segment after 12 weeks, while radiolucent areas showed still a partial loss of regular trabecular structure, with rare signs of remodelling and restoration. Despite qualitative alteration of the trabecular bone structure within the fusion site, the massive anterior heterotopic bone formation led to a substantial increase in mechanical stiffness compared to the autograft group. Copyright © 2015 John Wiley & Sons, Ltd.